Active Cycle Of Breathing Technique (ACBT) Improves Lung Function in Tuberculosis Patients - Nasya Adistya Islami; Istiroha Istiroha; Mono Pratiko Gustomi (Health Gate, 2026)
Background: pulmonary tuberculosis causes permanent structural damage to lung tissue through chronic inflammation and fibrosis, which leads to decreased lung elasticity, airway narrowing, and impaired gas exchange, which are the basis for the decline in lung function. One of the promising rehabilitation techniques is the Active Cycle of Breathing Technique. Objective: this study aims to determine and analyze the effect of administering the Active Cycle of Breathing Technique on the lung function of pulmonary tuberculosis patients. Methods: quantitative research using a Quasi-Experimental research design with a pre-test-post-test control group design, the sampling technique in this study used purposive sampling in 60 people. The instruments using observation sheets of lung function measurement results. Data analysis used the Wilcoxon signed rank test. Results: the study showed that there was an effect of administering the Active Cycle of Breathing Technique on pulmonary function of tuberculosis. The results of the Wilcoxon signed rank test statistical test showed an effect of the ρ value in the treatment group of 0.000 (α <0.05).  Conclusion: these findings suggest that administering Active Cycle of Breathing can improve lung function in tuberculosis patients. This study emphasizes that pharmacological therapy alone without additional respiratory rehabilitation interventions is insufficient to optimize lung function improvement.